Antigen-specific IL-2 secretion correlates with NK cell responses after immunization of Tanzanian children with the RTS,S/AS01 malaria vaccine. - Horowitz, A; Hafalla, J; King, E; Lusingu, J; Dekker, D; Leach, A; Moris, P; Cohen, J; Vekemans, J; Villafana, T; Corran, P; Bejon, P; et al. (2012)
RTS,S/AS01, a vaccine targeting pre-erythrocytic stages of Plasmodium falciparum, is undergoing clinical trials. We report an analysis of cellular immune response to component Ags of RTS,S-hepatitis B surface Ag (HBs) and P. falciparum circumsporozoite (CS) protein-among Tanzanian children in a phase IIb RTS,S/AS01(E) trial. RTS,S/AS01 (E) vaccinees make stronger T cell IFN-γ, CD69, and CD25 responses to HBs peptides than do controls, indicating that RTS,S boosts pre-existing HBs responses. T cell CD69 and CD25 responses to CS and CS-specific secreted IL-2 were augmented by RTS,S vaccination. Importantly, more than 50% of peptide-induced IFN-γ(+) lymphocytes were NK cells, and the magnitude of the NK cell CD69 response to HBs peptides correlated with secreted IL-2 concentration. CD69 and CD25 expression and IL-2 secretion may represent sensitive markers of RTS,S-induced, CS-specific T cells. The potential for T cell-derived IL-2 to augment NK cell activation in RTS,S-vaccinated individuals, and the relevance of this for protection, needs to be explored further.